Teachers' and students' beliefs in mathematics at State Senior High School 5 Semarang - Muhtarom, Muhtarom; Juniati, Dwi; Siswono, Tatag Yuli Eko; Rahmatika, Ismi (Jurnal Riset Pendidikan Matematika, 2018)
The aim of this research was to discover the relationship between teachers' and students' beliefs in mathematics. The sample consisted of two mathematics teachers, twenty eight students from 10th grade natural science 6 (X IPA 6) and twenty eight students from 10th grade natural science 10 (X IPA10) at state senior high school 5 Semarang. The data were collected from questionnaires and guided interviews on beliefs about mathematics. The research results showed that both of the mathematics teachers had platonist beliefs. It was found specifically that 4.76% of students in class X IPA 6 consistently had instrumentalist beliefs, 85.71% were consistent with their platonist beliefs, and 9.52% consistently had problem solving beliefs; while in class X IPA 10, 4.76% consistently showed instrumentalist beliefs, 80.95% were consistent with their platonist beliefs, and 14.29% consistently had problem solving beliefs. This indicates that there is a relationship between teachers' and students' beliefs, namely the tendency towards platonist beliefs; and also that the teacher's beliefs influence the student's beliefs.